Penciptaan Awal Alam Raya - Najmudin, Salman; Apipudin, Apipudin; Ahmad, Nurwadjah; Yuda, Dendi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
From several theories that are widely expressed by experts about the beginning of the creation of the universe, as well as information about the universe both from the scientific or scientific side. This makes us as writers, want to retrace the understanding of how the concept of the beginning of the creation of the universe from the Qur'an or science, and understand all the contents of the universe that have been created in accordance with the Qur'an Hadith. This study aims to determine the conceptualization of the beginning of the creation of the universe in terms of the Qur'an or science. And to know the content of the universe that was created through the perspective of the Qur'an and Hadith. This research uses historical research methods assisted by using the Big Bang theory, and scientific interpretation theory. This research will help readers know the beginning of the creation of the universe according to the Qur'an and science and know the content of the universe according to the Qur'an and hadith.